Modeling the Predictors of Nurses’ Research Use in Canadian Long-Term Care Homes - Demery Varin, Melissa (Université d'Ottawa / University of Ottawa, 2018)
Factors affecting the use of research evidence by nurses in long-term care (LTC) settings are largely unknown. In this thesis nurses referred to registered nurses (RNs) and licensed practical nurses (LPNs). A secondary analysis of data (n=756 nurses) from the Translating Research in Elder Care program was performed to construct Generalized Estimating Equation models of the predictors of nurses' self-reported instrumental, conceptual and persuasive research use. Positive attitudes towards research and better access to structural and electronic resources predicted all three kinds of research use. Additional statistically significant predictors suggest that individual variables play a more prominent role than contextual variables in predicting conceptual and persuasive use of research evidence, while instrumental research use is predicted equally by individual and organizational variables.
Keywords: Research use; Nurses; Long-term care; Context; Alberta Context Tool; TREC